Characterization of Polymeric Chemiresistors for Gas Sensor - Budi Gunawan; Muhammad Rivai; Hendro Juwono (Universitas Ahmad Dahlan, 2012)
Polymer is a non conductive materialthat can be conductive with carbon black filler to form polymer-carbon composite. polymer-carbon composite’s resistance changes with gas. The conductivity of polymer-carbon composite is influenced by several factors,i.e. type of gas, volume of gas, temperature and humidity.. This research characterizes the polymer-carbon composite sensor from 6 types of polymers: PEG6000, PEG20M, PEG200, PEG1540, Silicon and Squelene. The sensors are treated with Aceton, Aceton Nitril, Benzene, Etanol, Methanol, Ethyl Aceton, Chloroform, n-Hexan and Toluene. This characterization are grouped into 4 cluster according to their selectivity, sensitivity, influence of temperature and humidity. sensors are put in an isolated chamber which is connected to data acquisition with the variations of temperature, humidity, type and volume of gas. Correspondence analysis and regression are used to process the data. Test results found that each sensor showed different sensitivity and selectivity towards particular type of gas. Resistance of sensors increases with rising temperature and humidity environment with order 2 and order 3 polynomial equation